Mesenchymal Stem Cell-Derived Exosomes: The New Frontier for the Treatment of Intervertebral Disc Degeneration - Veronica Tilotta; Gianluca Vadalà; Luca Ambrosio; Fabrizio Russo; Claudia Cicione; Giuseppina Di Giacomo; Rocco Papalia; Vincenzo Denaro (Applied Sciences, 2021)
Low back pain (LBP) is one of the most frequent symptoms associated with intervertebral disc degeneration (IDD) and affects more than 80% of the population, with strong psychosocial and economic impacts. The main cause of IDD is a reduction in the proteoglycan content within the nucleus pulposus (NP), eventually leading to the loss of disc hydration, microarchitecture, biochemical and mechanical properties. The use of mesenchymal stem cells (MSCs) has recently arisen as a promising therapy for IDD. According to numerous reports, MSCs mediate their regenerative and immunomodulatory effects mainly through paracrine mechanisms. Recent studies have suggested that extracellular vesicles (EVs) extracted from MSCs may be a promising alternative to cell therapy in regenerative medicine. EVs, including exosomes and microvesicles, are secreted by almost all cell types and have a fundamental role in intercellular communication. Early results have demonstrated the therapeutic potential of MSCs-derived EVs for the treatment of IDD through the promotion of tissue regeneration, cell proliferation, reduction in apoptosis and modulation of the inflammatory response. The aim of this review is to focus on the biological properties, function, and regulatory properties of different signaling pathways of MSCs-derived exosomes, highlighting their potential applicability as an alternative cell-free therapy for IDD.